Characterization of excitatory and inhibitory neuron activation in the mouse medial prefrontal cortex following palatable food ingestion and food driven exploratory behavior - Gaykema, Ronald P. A.; Nguyen, Xuan-Mai T.; Boehret, Jessica M.; Lambeth, Philip S.; Joy-Gaba, Jonathan; Warthen, Daniel M.; Scott, Michael M. (Frontiers in Neuroanatomy, 2014)
The medial prefrontal cortex (mPFC) is implicated in aspects of executive function, that include the modulation of attentional and memory processes involved in goal selection. Food-seeking behavior has been shown to involve activation of the mPFC, both during the execution of strategies designed to obtain food and during the consumption of food itself. As these behaviors likely require differential engagement of the prefrontal cortex, we hypothesized that the pattern of neuronal activation would also be behavior dependent. In this study we describe, for the first time, the expression of Fos in different layers and cell types of the infralimbic/dorsal peduncular (IL/DP) and prelimbic/anterior cingulate (PL/AC) subdivisions of mouse mPFC following both the consumption of palatable food and following exploratory activity of the animal directed at obtaining food reward. While both manipulations led to increases of Fos expression in principal excitatory neurons relative to control, food-directed exploratory activity produced a significantly greater increase in Fos expression than observed in the food intake condition. Consequently, we hypothesized that mPFC interneuron activation would also be differentially engaged by these manipulations. Interestingly, Fos expression patterns differed substantially between treatments and interneuron subtype, illustrating how the differential engagement of subsets of mPFC interneurons depends on the behavioral state. In our experiments, both vasoactive intestinal peptide- and parvalbumin-expressing neurons showed enhanced Fos expression only during the food-dependent exploratory task and not during food intake. Conversely, elevations in arcuate and paraventricular hypothalamic fos expression were only observed following food intake and not following food driven exploration. Our data suggest that activation of select mPFC interneurons may be required to support high cognitive demand states while being dispensable during food intake.